A New Avenue to the Synthesis of Symmetrically Substituted Pyridines Catalyzed by Magnetic Nano–Fe3O4: Methyl Arenes as Sustainable Surrogates of Aryl Aldehydes. Issue 31 (20th August 2019) - Gajaganti, Somaiah; Kumar, Dhirendra; Singh, Sundaram; Srivastava, Vandana; Allam, Bharat Kumar
Abstract: A straightforward strategy has designed for the efficient synthesis of 2, 4, 6–triarylpyridines via a three component reaction of acetophenone, methyl arenes and ammonium acetate. The total transformation is successfully achieved using a magnetic nano–Fe3 O4 . The method developed is sustainable, using low cost feed stocks, operationally simple, and provide good to excellent yields. Abstract : A direct approach has developed for the efficient multicomponent synthesis of 2, 4, 6–triarylpyridines from an acetophenone, methyl arenes and ammonium acetate using a magnetic nano–Fe3 O4 . The present approach is sustainable, using cheap feed stocks, operationally simple, and enables good to excellent yields.